2017
DOI: 10.1111/nyas.13318
|View full text |Cite
|
Sign up to set email alerts
|

Recent theoretical, neural, and clinical advances in sustained attention research

Abstract: Models of attention often distinguish between attention subtypes, with classic models separating orienting, switching, and sustaining functions. Compared to other forms of attention, the neurophysiological basis of sustaining attention has received far less attention yet it is known that momentary failures of sustained attention can have far ranging negative impacts in healthy individuals and lasting sustained attention deficits are pervasive in clinical populations. In recent years, however, there has been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
161
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 208 publications
(192 citation statements)
references
References 208 publications
11
161
1
7
Order By: Relevance
“…This cognitive function implicates a complex neural network including the prefrontal cortex (Cona et al, 2015;Gonneaud et al, 2014) and premotor and supplementary motor cortex (Cona et al, 2015;Hashimoto, Umeda, & Kojima, 2011). Similarly, sustained attention is a multicomponent mental process involving distributed brain regions including the prefrontal cortex and premotor and supplementary motor cortex (Fortenbaugh, DeGutis, & Esterman, 2017;Langner & Eickhoff, 2013). Based on these prior findings, one may speculate that aberrant interhemispheric communications between bilateral prefrontal cortex and bilateral premotor and supplementary motor cortex, resulting from abnormal fiber connections, may contribute to the dysfunctions of prospective memory and sustained attention in OSA patients.…”
Section: Tamentioning
confidence: 99%
“…This cognitive function implicates a complex neural network including the prefrontal cortex (Cona et al, 2015;Gonneaud et al, 2014) and premotor and supplementary motor cortex (Cona et al, 2015;Hashimoto, Umeda, & Kojima, 2011). Similarly, sustained attention is a multicomponent mental process involving distributed brain regions including the prefrontal cortex and premotor and supplementary motor cortex (Fortenbaugh, DeGutis, & Esterman, 2017;Langner & Eickhoff, 2013). Based on these prior findings, one may speculate that aberrant interhemispheric communications between bilateral prefrontal cortex and bilateral premotor and supplementary motor cortex, resulting from abnormal fiber connections, may contribute to the dysfunctions of prospective memory and sustained attention in OSA patients.…”
Section: Tamentioning
confidence: 99%
“…Several studies have linked vascular diseases to disruption in DMN (Damoiseaux & Greicius, 2009;Mayda, Westphal, Carter, & DeCarli, 2011;Papma et al, 2013). While greater DMN activity is commonly associated with being off-task or resting, recent studies have shown associations between DMN activity and cognition (Spreng, 2012;Vatansever, Menon, Manktelow, Sahakian, & Stamatakis, 2015), including the ability to maintain sustained attention over time (Esterman, Noonan, Rosenberg, & DeGutis, 2012;Fortenbaugh, DeGutis, & Esterman, 2017;Kucyi, Esterman, Riley, & Valera, 2016). Studies have also observed reduced cerebrovascular function (i.e., Cerebral Blood Flow) in DMN regions in AD (Alsop, Detre, & Grossman, 2000;Jagust & D'Esposito, 2009;Johnson et al, 2005), mild cognitive impairment (MCI) (Duschek & Schandry, 2007;Johnson et al, 2005), and in older adults without cognitive impairment (Claus et al, 1998;Jagust & D'Esposito, 2009;Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As attention underlies many other higher-level cognitive functions, attentional impairments can result in deficits of diverse cognitive functions (Fortenbaugh et al, in press). Thus, improvement of attentional control has widespread clinical appeal.…”
Section: Introductionmentioning
confidence: 99%
“…Converging evidence directly implicates a set of frontal and parietal regions, termed the dorsal attention network (DAN), in attentional control (i.e., preparing, initiating, and maintaining goal-directed attentional control; e.g., Corbetta et al, 2000; Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999; Langner & Eickhoff, 2013; Fortenbaugh et al in press). Recently, the DAN has been shown to include both cortical and cerebellar nodes (Brissenden, Levin, Osher, Halko, & Somers, 2016).…”
Section: Introductionmentioning
confidence: 99%